2019
DOI: 10.1002/anie.201907209
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Carboligation with Whole‐Cell Biocatalysts in Pickering Emulsion

Abstract: Pickering emulsions (PEs) are particle-stabilized multiphase systems with promising features for synthetic applications.D escribed here is an ovel, simplified set-up employing catalytically active whole cells for simultaneous emulsion stabilization and synthetic reaction. In the stereoselective carboligation of benzaldehyde to (R)-benzoin catalyzed by abenzaldehyde lyase in E. coli, the set-up yielded maximum substrate conversion within very short time,while economizing material demand and waste.F ormation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Pickering emulsions were extensively studied in the 20th century. Their high colloidal stability and controllable droplet size make them particularly suitable for single-cell encapsulation ( Yaakov et al, 2018 ), ( Bashir et al, 2016 ), ( Chen et al, 2015 ), ( Röllig et al, 2019 ). The stability of Pickering emulsions is governed by different parameters including their particle concentration, the wettability of the particles (oil/water volume fraction), and destabilization mechanisms ( Ortiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pickering emulsions were extensively studied in the 20th century. Their high colloidal stability and controllable droplet size make them particularly suitable for single-cell encapsulation ( Yaakov et al, 2018 ), ( Bashir et al, 2016 ), ( Chen et al, 2015 ), ( Röllig et al, 2019 ). The stability of Pickering emulsions is governed by different parameters including their particle concentration, the wettability of the particles (oil/water volume fraction), and destabilization mechanisms ( Ortiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidoreductases, including alcohol dehydrogenases and peroxidases as well as alcohol and phenol oxidases were found to be active in neat organic solvents in the 1980s, and further studies on oxidoreductases were conducted during this decade . Examples with lyases comprise hydroxynitrile lyases, cyclases, decarboxylases, hydroperoxide lyases and benzaldehyde lyases …”
Section: Introductionmentioning
confidence: 99%
“…In fact, Röllig et al. reported the stabilisation of emulsions with E. coli cells containing a lyase for the stereoselective carboligation of benzaldehyde to ( R )‐benzoin [43] . Herein, however, we prefer silica particles to be the sole emulsifier.…”
Section: Resultsmentioning
confidence: 98%
“…[42] As aresult, it can be surface-active at the oil-water interface.I nf act, Rçllig et al reported the stabilisation of emulsions with E. coli cells containing al yase for the stereoselective carboligation of benzaldehyde to (R)-benzoin. [43] Herein, however,w ep refer silica particles to be the sole emulsifier.Therefore,alow concentration of E. coli cells containing OxdB of 0.025 wt. %w as selected to prepare emulsions.…”
Section: Introductionmentioning
confidence: 99%